2015
DOI: 10.1007/s11144-015-0861-0
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of dyes by a novel TiO2/u-RuO2/GNS nanocatalyst derived from Ru/GNS after its use as a catalyst in the aerial oxidation of primary alcohols (GNS = graphene nanosheets)

Abstract: Ruthenium nanoparticles (RuNPs) supported on graphene nanosheets (GNS) composite (Ru/GNS) was prepared by dry synthesis method and was used as a nanocatalyst for the aerial oxidation of various primary alcohols. The Ru/GNS was highly efficient, selective, stable and heterogeneous in nature. Owing to the high stability of the used catalyst (u-Ru/GNS), it was further applied in a different catalytic system viz photocatalytic degradation, after suitable modifications. We have obtained a novel TiO 2 /u-RuO 2 /GNS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Generally, the catalysis systems are homogeneous, heterogeneous, and enzymes. [1] Catalysis is mostly used in organic transformations such as oxidation, [2,3] reductions, [4] CÀ H activation as well as coupling reactions (Suzuki, Heck, Sonogashira, Still, Negishi, Kumuda, Sarylation, N-arylation, and O-arylation). Many researchers used homogeneous catalysts in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the catalysis systems are homogeneous, heterogeneous, and enzymes. [1] Catalysis is mostly used in organic transformations such as oxidation, [2,3] reductions, [4] CÀ H activation as well as coupling reactions (Suzuki, Heck, Sonogashira, Still, Negishi, Kumuda, Sarylation, N-arylation, and O-arylation). Many researchers used homogeneous catalysts in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The AgNPs/e-HHP, AuNPs/e-HHP, CuNPs/e-HHP, NiNPs/e-HHP, and RuNPs/e-HHP were employed for the coupling of amines, N -oxidation of tertiary amines, aza -Michael reaction, imines synthesis, and oxidation of alcohols, respectively. These reactions are highly important in organic chemistry. , The products are often used for the preparation of various industrially important fine chemicals, cosmetics, pharmaceuticals, agricultural chemicals, natural products, and antibiotics. In addition, they are found to play key role as catalysts, protecting agents, oxidants, and auxiliary agents in various organic reactions including asymmetric synthesis. ,, Supported transition MNPs including V, Cu, Fe, Au, Ru, Ag, Pd, Pt, Co, Zn, and Ni have been reported as catalysts for various organic transformations. , …”
Section: Resultsmentioning
confidence: 99%
“…Chemically stable carbon nanomaterials (CMs) such as activated carbons (ACs), carbon nanotubes (CNTs), graphene, and fullerenes have also been introduced as catalyst supports for MNPs. For example, our research group reported many CM-supported MNPs, including RuO 2 NRs/GNPs, Au–Ag/graphene, RuNPs/GNS, CuO/MWCNT, RuO 2 /MWCNTs, GNS/CuO, RuO 2 /SWCNTs, TiO 2 / u -RuO 2 /GNS, and GNS-RuO 2 NPs, as highly efficient catalysts. Tzirakis and co-workers prepared γ-alumina supported [60]-fullerene catalysts and employed them for photooxidation of alkenes.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Immobilization of metal NPs on the surface of GNS was found to play a very useful role in different fields such as energy, biomedical, catalysis and sensors. [28][29][30]18 Particularly, the Cu NPs-decorated GNS are frequently utilized for various applications due to their outstanding activity. 31,32 For example, Fakhri et al 33 prepared Cu NPs supported on graphene oxide via reduction method and found it as a highly active and recyclable catalyst for the synthesis of formamides and primary amines.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Few-layer graphene nanosheets (GNS) have attracted tremendous attention due to their unique physicochemical properties such as high surface area, chemical stability, electrical conductivity and dispersion in solvents. , Immobilization of metal NPs on the surface of GNS was found to play a very useful role in different fields such as energy, biomedical, catalysis and sensors. , Particularly, the Cu NPs-decorated GNS are frequently utilized for various applications due to their outstanding activity. , For example, Fakhri et al prepared Cu NPs supported on graphene oxide via reduction method and found it as a highly active and recyclable catalyst for the synthesis of formamides and primary amines. Wang and co-workers found that the decoration of CuO on graphene showed high performance as an anode material in lithium-ion batteries.…”
Section: Introductionmentioning
confidence: 99%